Nitrogen uptake, growth rate and yield of tomatoes under saline conditions. - Al-Rawahy, Salim Ali (The University of Arizona., 1989)
Results of two studies are reported here, a greenhouse study and a field study. In the greenhouse study, dry matter yield and nitrogen (total and 15N) uptake of leaves, stems and roots of tomato plants (Lycopersicum esculentum Mill., cv. Columbia) subjected to saline stress by NaCl were studied. The integrated effects of responses of these tissues to salinity on the whole plant basis and levels of Na⁺, Cl⁻ and K⁺ accumulation in these tissues were also studied. The treatments consisted of low (control, 0.3 bar), medium (4.3 bars), and high (8.3 bars) salinity. The saline treatments were prepared by adding NaCl to nutrient solution in sand culture. The plants were 80 days old at the start of the treatments and each was in a pot containing 1.8 kg of quartz sand. The ¹⁵N was provided to plants by adding K¹⁵NO₃ to the pots and the 15N treatment continued with the saline treatments up to 30 days. The plants were harvested at each 5-day interval during the treatment period. Dry matter production and nitrogen (total and ¹⁵N) uptake were significantly lower for saline treatments as compared with the control. Differences in dry matter production and ¹⁵N uptake on whole plant basis appeared in the latter part of the treatment period between the two saline treatments. For most of the parameters studied, the leaves were found to be affected most by salinity, the roots were intermediate in their response and the stems were the least affected by salinity. The effect of salinity on the studied parameters were attributed to osmotic effects and specific ion effects of Na⁺ and/or Cl⁻. A field study with two cultivars--Columbia and Pearson was conducted at the Safford Agricultural Center. Three N treatments were used: 0 kg N/ha, 84 kg N/ha and 168 kg N/ha and two treatments consisting of two water sources--river water with an EC of 1.15 dS/m and more saline well water of EC of 2.21 dS/m. Columbia had a significantly higher yield of tomatoes than Pearson for both water types. The N treatments had no effect on tomato yield apparently due to high residual N remaining in the field from the previous crop. Commercially acceptable fresh market yields were approached with both varieties and waters in spite of moderate salinity and sodium under heavy textural soil conditions, high temperatures and the presence of certain diseases in the area.